Pojęcie i znaczenie telepracy jako nowoczesnej formy zatrudnienia (aspekty prawnospołeczne) - Chobot, Andrzej (Wydział Prawa i Administracji UAM, 1996)
Following the progress in information theory and telecommunication, telework appeared as a work organization system at the end of the 60s. It allows people to work at a distance from the employer. It adds to productivity and effectiveness of enterprises, helps relocation of jobs in economically backward regions and positively assists employment (it helps part time job, job-sharing, work-sharing, office-sharing, job splitting). However, the introduction of telework on a wider scale may lead to disintegration of the collective forms of workers' organizations, which in due course may cause atomization of labour and exclusion of a part of the population from the organized social dialogue. The author analyses the definitions and particular types of telework, including home based telework, the legal status of home based workers, and their elementary employment rights.
The notion and meaning of telework as a modern form of employment